Associations between glucocorticoids, antiphospholipid antibodies and femur head necrosis in patients with SLE: a directed acyclic graph-based multicentre study. (March 2021) - Chen, Shengbao; Cai, Qianying; Xu, Yanjun; Fu, Qiong; Feng, Yong; Chen, Xiaoxiang; Dai, Shengming; Zhao, Dongbao; Zhan, Ce; Xu, Weidong; Wang, Jiwei; Wang, Yang; et al.
Background: Osteonecrosis of the femoral head (ONFH) remains a major cause of disability in patients with systemic lupus erythematosus (SLE) and seriously impairs quality of life. This study aimed to investigate associations between glucocorticoids (GCs), antiphospholipid antibodies (aPLs), and ONFH in patients with SLE. Methods: We conducted a multicentre cohort study on patients with SLE and used a directed acyclic graph-based analysis strategy. Details of GC therapy, aPLs status, other drug administration and other SLE-related characteristics were collected. ONFH occurrence during follow-up was determined by magnetic resonance imaging. Multivariable logistic regression and generalized estimating equation models were performed to assess their effects on ONFH, and a simplified scoring system comprising these factors for short- and medium-term SLE-ONFH prediction was developed by receiver operating characteristic curve analysis. Results: Of 449 SLE patients with a median follow-up duration of 5.3 years, 41 (9.1%) developed ONFH. Independently risk factors of SLE-ONFH including: average daily GC dose with an adjusted odds ratio (aOR) of 1.1 and 95% confidence interval (CI) of 1.0–1.1; GC therapy duration (3–5 years: aOR 3.3, 95% CI 1.4–7.8; >5 years: aOR 8.0, 95% CI 3.3–19.4); initial intravenous GC (aOR 4.4, 95% CI 1.9–10.1); positive aPLs (aOR 2.8, 95% CI 1.4–5.8); and Arterial hypertension secondary to GC usage (aOR 5.2, 95% CI 1.4–19.1). And we successfully developed the simplified scoring system (SCORE model) with an area under the curve of 0.88 (95% CI 0.82–0.94). Conclusion: Based on the risk factors involved in the development of SLE-ONFH, a novel SCORE model was developed, which might be helpful for risk stratification of SLE-ONFH in clinical practice.